The Relationship Between Lipoprotein-Associated Phospholipase-A2 and Coronary Artery Aneurysm in Children With Kawasaki Disease - Cheng, Zhenli; Weng, Haobo; Zhang, Jing; Yi, Qijian (Frontiers in Pediatrics, 2022)
Background: Coronary artery lesions including aneurysm, as the most severe complications of Kawasaki disease (KD), remain of great concern. Lipoprotein-associated phospholipase A2 (Lp-PLA2) is implicated in the regulation of inflammatory response and lipid metabolism. Since excessive inflammatory response and aberrant lipid metabolism have involved in the development of KD, we in this study sought to investigate the relationship between coronary artery aneurysm (CAA) and Lp-PLA2 and other blood parameters in children with KD. Methods: The participants included 71 KD patients, 42 healthy controls (HCs) and 15 febrile controls (FCs). KD patients were divided into KD-CAA (KD with CAA) group and KD-NCAA (KD without CAA) group. Serum Lp-PLA2 levels were measured using enzyme-linked immunosorbent assays. Other routine clinical parameters were also detected. Results: Serum Lp-PLA2 levels in KD group (4.83 μg/mL (3.95-6.77)) were significantly higher than those in HC (1.48 μg/mL (0.98-2.14)) and FC (2.65 μg/mL (0.52-3.53)) groups. KD-CAA group (5.56 μg/mL (4.55-22.01)) presented substantially higher serum Lp-PLA2 levels as compared with KD-NCAA group (4.64 μg/mL (2.60-5.55)). In KD group, serum Lp-PLA2 level was positively related with erythrocyte sedimentation rate, the levels of leukocytes, platelets, albumin, creatine kinase-MB, and D-dimer, and the Z-scores of left main CA, right CA, left anterior descending CA, and left circumflex CA; and negatively related with mean corpuscular hemoglobin concentration and mean platelet volume. Moreover, receiver operating characteristic curves showed that Lp-PLA2 exhibited superior and moderate diagnostic performance for distinguishing KD patients from HC and FC ones, respectively, and possessed the potential ability to predict the occurrence of CAAs in KD. Conclusion: Lp-PLA2 may involve in the pathogenesis of KD and the formation of CAAs, and thus may serve as a potential diagnostic biomarker for KD.